Laboratory signs of carbohydrate malabsorption in early age children with rotavirus infection - N. V. Vorobiova; O. V. Usachova (Zaporozhye State Medical University, 2021)
The aim - to determine the laboratory manifestations of carbohydrate malabsorption syndrome in the dynamics of rotavirus infection in early age children and to identify the factors that influence its severity. Materials and methods. The study included 60 breastfed children aged 1-24 months with rotavirus infection, who underwent pH-metry of feces, semi-quantitative determination of total carbohydrates (Benedict's method), lactose (Malfatti method) and glucose (test systems Glucophan) in feces on the 2nd, 3rd, 5th, 7th and 10th days of the disease. Results. Carbohydrate malabsorption syndrome was observed in 98.3% of patients. The level of fecal carbohydrates increased on the second-third day to a clinically significant 0.50 [0.20; 1,50] %, reached its maximum in the midst of the disease - from the fifth to the seventh day (0.75 [0.50; 1.65] % and 0.87 [0.40; 1.65] %, respectively), decreasing during convalescence to 0.50 [0.20; 1.50] % (P < 0.05 relative to the 10th day), but remained elevated in 81.7 % of patients (P < 0.05 relative to healthy children). Lactase deficiency and glucose malabsorption (P < 0.05 relative to healthy children) were observed throughout the RVI period. At all stages of RVI there was a strong direct correlation between the total level of carbohydrates and lactose in the feces (on the second, third, fifth, seventh and tenth days r = 0.91; r = 0.86; r = 0.91; r = 0.89, respectively). The age dependence of the severity of laboratory indicators of carbohydrate malabsorption was established. Children in the first 6 months had the highest maximum levels of carbohydrates and fecal lactose - 1.75 [1.00; 2.00] % and 3.50 [2.00; 4.00] + respectively (P < 0.05 relative to 12-24 months children) and significantly higher values of these indicators in the dynamics of RVI (P < 0.05 relative to 12-24 months children) for the second-third, fifth and the tenth day). Children with concomitant food allergies, atopic dermatitis and iron deficiency anemia had 2.0 and 1.5 times higher maximum levels of carbohydrates and lactose in the stool, respectively (P < 0.05), as well as higher values of these indicators in the dynamics of the disease - on the third and fifth days (P < 0.05). Conclusions. The vast majority of young patients with rotavirus infection have carbohydrate malabsorption syndrome, which occurs from the first days of the disease and is most pronounced on the fifth to seventh day (P < 0.05 relative to the 10th day), realized mainly due to lactase deficiency. The most pronounced carbohydrate malabsorption syndrome and lactase deficiency in the dynamics of the disease are present in children of the first six months of life. Factors that increase the severity of carbohydrate malabsorption due to secondary lactase deficiency in the acute period of rotavirus infection are concomitant food allergies, atopic dermatitis and iron deficiency anemia.